Factors Affecting the Working Status of Elderly People in Dhurkot Rural Municipality, Gulmi - Kunwar, Thaneshwar (Nepal Population Journal, 2026)
This study looked at the variables affecting the employment status of senior citizens in Nepal's Gulmi District's Dhurkot Rural Municipality. The effects of sociodemographic factors were examined using binary logistic regression in a cross-sectional survey of senior citizens. The findings showed a substantial relationship between age and labor involvement. There was no significant difference in the likelihood of being employed between the age groups of 65 and 69 (OR = 4.95; 95% CI: 1.19–20.47) and 75 and older (OR = 4.12; 95% CI: 1.19–14.28) as compared to the reference group (60–64 years). Occupation did not show any statistically significant association, as household work (OR = 0.74), tilling and sewing (OR = 1.27), and other occupations (OR = 0.71) were comparable to agriculture. These findings suggest that elderly individuals, particularly in the 65–69 and 75+ age groups, continue working largely out of necessity, highlighting the persistence of agricultural dependency and the limited role of occupational diversification. The study underscores the importance of strengthening social protection systems and developing non-agricultural livelihood opportunities to reduce the economic vulnerability of older populations in rural Nepal.